2000
DOI: 10.3109/07357900009012201
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Cytotoxic Effects of Vinorelbine and Paclitaxel in Vitro

Abstract: Empiric combinations of vinca alkaloids with taxanes have been recently used in clinical oncology. To enhance the activity of these two classes of agents, we evaluated the sequence and duration of exposure, looking for synergistic effects. Cell lines DU 145, PC 3, LnCaP, LL 86, MCF7wt, and MCF7/ADR (NCI/ADR-RES) were incubated with varying concentrations of paclitaxel or vinorelbine. Cytotoxicity was evaluated by a semiautomated MTT (3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide) method. Synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Synergy occurred when vinorelbine was applied before paclitaxel, or when the drugs were applied concurrently and left for 96 h (8). Antagonism was observed when the order was reversed (80) or with alternating applications starting with either agent (81). The opposite was observed in studies of human lung cancer lines, where synergy was observed with alternating application (82).…”
Section: Discussionmentioning
confidence: 86%
“…Synergy occurred when vinorelbine was applied before paclitaxel, or when the drugs were applied concurrently and left for 96 h (8). Antagonism was observed when the order was reversed (80) or with alternating applications starting with either agent (81). The opposite was observed in studies of human lung cancer lines, where synergy was observed with alternating application (82).…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to paclitaxel, vinorelbine binds microtubules and prevents their polymerisation, thus interfering with mitosis (Krikorian and Breillout, 1991). Previous studies have demonstrated that independent of the type of effect by the antimicrotubule agent on microtubule assembly (polymerisation or depolymerisation), these drugs exhibit the ability to promote apoptosis in cancer cells (Wang et al, 1999bBudman et al, 2000;Charles et al, 2001;Fan et al, 2001;Liu et al, 2001). One of mechanisms of vinorelbine-induced apoptosis is thought to be the upregulation of p21 and p53.…”
mentioning
confidence: 99%
“…The rationale for administering vinorelbine in association with paclitaxel in anthracycline-pretreated breast cancer patients centres mainly on the documented activity of the two drugs in anthracycline refractory patients (Crown et al, 2002) and on the synergism of the cytotoxic effects of the two drugs in preclinical models (Photiou et al, 1997;Budman et al, 2000). The addition of infusional 5-FU might further increase the activity of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…All drugs were administered on an outpatient basis. Since preclinical data suggested that the sequence of administration of paclitaxel and vinorelbine was predictive for treatment efficacy (Photiou et al, 1997;Budman et al, 2000), vinorelbine infusion preceded paclitaxel infusion. Dose modifications were performed as follows: in case of myelosuppression, if the WBC count was p2500 ml À1 and/or the platelet count was less than 100 000 ml À1 , then 5-FU was continued but both paclitaxel and vinorelbine at that day were omitted.…”
Section: Treatment Schedulementioning
confidence: 99%
See 1 more Smart Citation